2018
DOI: 10.1016/j.jid.2018.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Vildagliptin Significantly Increases the Risk of Bullous Pemphigoid: A Finnish Nationwide Registry Study

Abstract: Philpott MP, Kealey T. Metabolic studies on isolated hair follicles: Hair follicles engaged in aerobic glycolysis and do not demonstrate the glucose fatty acid cycle. J Invest Dermatol 1990;96:875e9. Ramot Y, Mastrofrancesco A, Camera E, Desreumaux P, Paus R, Picardo M. The role of PPARgamma-mediated signalling in skin biology and pathology: new targets and opportunities for clinical dermatology. Exp Dermatol 2015;24:245e51.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
143
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(167 citation statements)
references
References 15 publications
18
143
6
Order By: Relevance
“…Likewise, a similar increase was also observed in a Japanese pharmacovigilance database, particularly among patients treated with vildagliptin, linagliptin, or teneligliptin (Arai, Shirakawa, Konishi, Sagawa, & Terauchi, 2018). Several observational studies (all case-control designs) have also been conducted and it was reported that a significantly increased or a trend towards an increased risk of BP is associated with the usage of DPP4is with odds ratios ranging between 1.58 and 3.16 (Benzaquen et al, 2018;Kridin & Bergman, 2018;Lee, Lee, Yoon, & Kim, 2019;Plaquevent, et al, 2019;Varpuluoma et al, 2018). Moreover, Benzaquen et al has reported that application of DPP4is increases the risk of BP of almost 3-fold, and the increase is associated with vildagliptin rather than other gliptins (Benzaquen et al, 2018).…”
Section: Dpp4/cd26 Inhibition and Bpsupporting
confidence: 60%
See 1 more Smart Citation
“…Likewise, a similar increase was also observed in a Japanese pharmacovigilance database, particularly among patients treated with vildagliptin, linagliptin, or teneligliptin (Arai, Shirakawa, Konishi, Sagawa, & Terauchi, 2018). Several observational studies (all case-control designs) have also been conducted and it was reported that a significantly increased or a trend towards an increased risk of BP is associated with the usage of DPP4is with odds ratios ranging between 1.58 and 3.16 (Benzaquen et al, 2018;Kridin & Bergman, 2018;Lee, Lee, Yoon, & Kim, 2019;Plaquevent, et al, 2019;Varpuluoma et al, 2018). Moreover, Benzaquen et al has reported that application of DPP4is increases the risk of BP of almost 3-fold, and the increase is associated with vildagliptin rather than other gliptins (Benzaquen et al, 2018).…”
Section: Dpp4/cd26 Inhibition and Bpsupporting
confidence: 60%
“…Increased risk in T2DM patients (Aouidad et al, 2013;Arai et al, 2018;Bene, et al, 2016;Benzaquen et al, 2018;Douros et al, 2019;Garcia et al, 2016;Kridin & Bergman, 2018;Lee et al, 2019;Plaquevent, et al, 2019;Varpuluoma et al, 2018) Taken together, these existing studies fail to strongly support the clinical application of DPP4is in either glucose control or β cell preservation in T1DM patients. The contrary conclusions obtained from the above clinic trials may be attributed to different baseline characteristics of the included patients (such as c-peptide levels, HbA1c, and disease duration), distinct follow-up lengths, different sample size, and other variables.…”
Section: Bpmentioning
confidence: 99%
“…Pharmacovigilance reports have reported mean latency periods ranging from 6 to 19 months. Varpuluoma and colleagues reported mean latency period between vildagliptin and BP onset of approximately 15 months. There are insufficient data to support whether BP is a drug‐induced adverse effect or whether DPPI brings out and exacerbates BP in those with underlying susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this large population‐based cohort study revealed that the use of DPP‐4 inhibitors was significantly related to an increased risk of BP with an aHR of 2.382 ( P = 0.017). The previous studies have elucidated the association between DPP‐4 inhibitors and BP . In 2019, a large population‐based cohort study of 8569 DPP‐4 inhibitor users and 160 205 non‐DPP‐4 inhibitor users was published by using the UK Clinical Practice Research Datalink .…”
Section: Discussionmentioning
confidence: 99%